Ukraine's Gas Arrears : Issues and Recommendations - Bisat, Amer. (Washington, D.C. : International Monetary Fund, 1996)
This paper discusses issues related to the gas arrears 'crisis' in Ukraine. It concludes that the problem, which can be traced to policy distortions, can be contained through an acceleration of structural reforms. The paper examines the nature of the contractual relations between Ukraine and its foreign suppliers; the role of the de facto government guarantee for gas import payments; the process of imposing financial discipline on non-payers; the nature of gas-related subsidy schemes; and the methods used in calculating domestic energy prices. An Appendix derives lessons from the Estonian case--an economy which, despite relatively similar initial conditions, avoided the emergence of energy payment difficulties. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the author(s) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet